2015
DOI: 10.3174/ajnr.a4288
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of the Peripheral Branches of the Mandibular Division of the Trigeminal Nerve on 3D Double-Echo Steady-State with Water Excitation Sequence

Abstract: BACKGROUND AND PURPOSE:Although visualization of the extracranial branches of the cranial nerves has improved with advances in MR imaging, only limited studies have assessed the detection of extracranial branches of the mandibular nerve (V3). We investigated the detectability of the branches of V3 on a 3D double-echo steady-state with water excitation sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 17 publications
2
35
0
1
Order By: Relevance
“…Similarly, a previous study showed that the 3D-DESS-WE sequence enabled uniform detectability of the peripheral branches of the cranial nerve by readers at various training levels. 10 There are several limitations in this study. First, our study consists of a relatively small number of deep lobe tumors (17.6%) compared with superficial lobe tumors.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Similarly, a previous study showed that the 3D-DESS-WE sequence enabled uniform detectability of the peripheral branches of the cranial nerve by readers at various training levels. 10 There are several limitations in this study. First, our study consists of a relatively small number of deep lobe tumors (17.6%) compared with superficial lobe tumors.…”
Section: Discussionmentioning
confidence: 92%
“…11 Another study showed that the 3D-DESS-WE sequence demonstrated excellent visualization of the entire course of the mandibular division of the trigeminal nerve in most patients. 10 Therefore, we routinely use the 3D-DESS-WE sequence to visualize the intraparotid facial nerve for preoperative evaluation. To our knowledge, there have been no previous studies evaluating the 3D-DESS-WE sequence for localizing parotid gland tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fujii et al (35) reported excellent visualization of the lingual and inferior alveolar branches of the trigeminal nerve with MR neurography, followed by good detection of the masseteric, buccal, and auriculotemporal branches, with poor detection of the mylohyoid nerve. At MR neurography, V3 is best seen on thick-slab MIP images in the straight coronal plane, V1 and V2 branches are best seen in the sagittal plane, while the IAN is best seen in the anterior oblique coronal plane.…”
Section: Trigeminal Nervementioning
confidence: 99%
“…13 Due to the small diameter of the nerve it becomes difficult to detect the nerve on magnetic resonance imaging. 14 The aim of this review is to discuss and make the clinicians aware of the anomalies of the MHN and its clinical implications.…”
Section: Introductionmentioning
confidence: 99%